Advanced numerical modelling of geogrid-reinforced rockfall protection embankments - Murashev, A.; Easton, M.; Kathirgamanathan, P. (My University, 2014)
Currently, empirical or simplified analytical methods are used to design such embankments. In order to assess behaviour of rockfall protection embankments in more detail, Opus carried out 3D numerical simulation using the finite element software ABAQUS. In the simulation process rock blocks were thrown onto a geogrid reinforced embankment at different impact angles. The effects of geogrid spacing, the presence of the steel facing mesh and impact angle have been investigated. The numerical simulation procedure can be used to develop and optimise the design of geogrid-reinforced rockfall protection embankments.
Keywords: Rockfall protection; Embankment; Finite element modelling; Geogrid